Sistem Pemantauan Gas Gunungapi Berbasis IoT dan Energi Surya untuk Mitigasi Bencana di Gunung Bromo - Hartawan Abdillah; Wahyu Andrian Kusuma; Mas Ahmad Baihaqi; Alief Muhammad; Indah Noor Dwi Kusuma Dewi (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2025)
This study presents the design of an IoT-based volcanic gas monitoring system powered by solar energy. The system integrates H₂S and CO₂ sensors with an ESP32 microcontroller, transmitting data in real time to a cloud dashboard via MQTT/HTTP protocols. A 100–300 Wp solar panel generated an average of 21 V and 2.1 A (≈529 Wh/day), significantly exceeding the sensor’s energy demand of ≈24 Wh/day. Field testing at Mount Bromo recorded average concentrations of H₂S = 0 ppm and CO₂ = 599 ppm, which are below hazardous thresholds but require continuous observation. The results demonstrate that the system is energy-efficient, stable under variable conditions, and effective in providing early warning alerts, thus supporting volcanic disaster mitigation and aligning with SDGs 9 and 13.